The Development of E-Leaflet Teaching Materials Using QR-Code in Human Excretory System Material - Bella Safira Salsabila; Nugroho Edi Kartijono (Journal of Biology Education, 2023)
The Covid-19 pandemic was caused by the SARS CoV-2 virus which resulted in changes in almost all aspects of people's lives in the world. One of them occurred in the field of education. In the education sector, the learning process takes place online and requires a variety of additional technologies to support the learning process. During the online learning process, teaching materials are also needed that are appropriate to the conditions that occur. The purpose of this research was to develop appropriate teaching materials for use during the Covid-19 pandemic. The type of research used is research development or Research and Development (R&D). The validation test results carried out by media experts were 94.53% and the material expert validation results were 90.43%. In small-scale product trials, the final test results showed that only 13.9% of students did not pass. In the practicality questionnaire responses, students showed that 19% of students considered this teaching material practical and 81% considered this teaching material very practical. Whereas in the large-scale trial conducted in 3 classes with a total of 108 students, the final test results showed that only 7.4% of students did not pass. In the response questionnaire given to the teacher, the percentage results were 96.35% which was included in the very valid category. In the student response questionnaire, 11% of students considered this teaching material practical and the remaining 89% of students considered this teaching material very practical. Based on the results of the research that has been done, it can be concluded that e-leaflet teaching materials using qr-codes on human excretory system material are feasible and practical to use in the online learning process during the Covid-19 pandemic.